2018
DOI: 10.3390/su10082811
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Social Factors That Determine Sustainable Consumption Behavior in the Community of Madrid

Abstract: This paper defines the social factors that determine sustainable behavior and identifies the elements that promote such behavior. These factors are external from the individual and causal regarding sustainable behavior, an area that receives little attention in literature. It uses a theoretical model, based on existing research, which is tested through a questionnaire with 26 indicators adapted to the Spanish context. In an initial analysis, this model proposed, as determining social factors in the CCS, aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 41 publications
4
45
0
1
Order By: Relevance
“…For example, since obese people eat more and are more likely to use cars than to walk, the obese population could increase the demand for food, fuel, etc. [1][2][3]44]. As of today, only Chile uses warning messages, but the results of this research suggest that more countries should use warning messages, which is consistent with previous findings [11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…For example, since obese people eat more and are more likely to use cars than to walk, the obese population could increase the demand for food, fuel, etc. [1][2][3]44]. As of today, only Chile uses warning messages, but the results of this research suggest that more countries should use warning messages, which is consistent with previous findings [11][12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…Frugality was measured using four items adapted from [48] which is cross-referenced from the study [27]. Sustainable Consumption Behavior was measured using three items adapted from [112], and two items adapted from [113]. All adjusted constructs measure with item details and their sources are shown in Appendix A.…”
Section: Measurement Of Constructsmentioning
confidence: 99%
“…was measured using three items adapted from [112], and two items adapted from [113] SCB2. How motivated do you feel to make changes in your lifestyle in search of more responsible consumption?…”
Section: Sustainable Consumption Behaviormentioning
confidence: 99%
“…They found that the main factors that explain a sustainability behavior are ascription of responsibility, universal values and personal intelligence. In Spain, the most important social factors that determine sustainable consumption behavior of individuals were found to be: environmental influences (e.g., traditions), education, information, and market conditions [23].…”
Section: Modeling Sustainable Behaviormentioning
confidence: 99%